2004
DOI: 10.1128/aem.70.4.2318-2322.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Five Membrane Filtration Methods for Recovery of Cryptosporidium and Giardia Isolates from Water Samples

Abstract: We evaluated the efficiency of five membrane filters for recovery of Cryptosporidium parvum oocysts and Giardia lamblia cysts. These filters included the Pall Life Sciences Envirochek (EC) standard filtration and Envirochek high-volume (EC-HV) membrane filters, the Millipore flatbed membrane filter, the Sartorius flatbed membrane filter (SMF), and the Filta-Max (FM) depth filter. Distilled and surface water samples were spiked with 10 oocysts and 10 cysts/liter. We also evaluated the recovery efficiency of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 33 publications
(39 reference statements)
4
40
0
1
Order By: Relevance
“…Minor modifications to the manufacturer's protocol were 133 made. Briefly, samples were subjected to five cycles of freeze-thaw (freezing each sample Using Envirochek filters (Pall Life Sciences, New South Wales, Australia), filtration of the 144 water samples was performed in accordance with the manufacturer's instructions, except 145 for some slight modifications as described by Wohlsen et al, (2004). The eluate was 146 subjected to the same genomic DNA extraction method detailed above.…”
Section: Genomic Dna Extraction 129mentioning
confidence: 99%
“…Minor modifications to the manufacturer's protocol were 133 made. Briefly, samples were subjected to five cycles of freeze-thaw (freezing each sample Using Envirochek filters (Pall Life Sciences, New South Wales, Australia), filtration of the 144 water samples was performed in accordance with the manufacturer's instructions, except 145 for some slight modifications as described by Wohlsen et al, (2004). The eluate was 146 subjected to the same genomic DNA extraction method detailed above.…”
Section: Genomic Dna Extraction 129mentioning
confidence: 99%
“…And so, different filter systems are applied for the filtration required in these methods. As it turned out, the efficiency of those methods, assessed in practice, shows different degrees of recovery of cysts and/or oocysts depending on the applied filter system (Wohlsen et al, 2004). These and many other studies show that these methods have got many restrictions.…”
Section: Development In the Methods Of Detectionmentioning
confidence: 92%
“…However, IMS is not only expensive; its performance is affected by the type of commercial kit used, pH, and dissociation procedures (Ware et al 2003). Earlier studies have shown various degrees of recovery efficiency for Cryptosporidium (Hsu et al 2001;Simmons et al 2001;Wohlsen et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…The 1622 method detects and calculates only Cryptosporidium oocysts in water samples; the 1623 method -Cryptosporidium oocysts and Giardia cysts, and introduces some improvements. However, the recovery of oocysts from environmental water samples with the use of these both methods has been reported to be very variable (Simmons et al 2001;Kuhn and Oshima 2002;Wohlsen et al 2004;Krometis et al 2009;Karim et al 2010). With regard to this fact, matrix spikes are routinely analysed to determine the influence of environmental matrices on the effectiveness of the methods for detecting target organisms (Francy et al 2004).…”
mentioning
confidence: 99%